Massive Pulmonary Hemorrhage from Bronchial Varix - Michael Agustin; Scott Shay; Jose Gonzalez; Pei Liu; Nancy Lentz; Anna Shapiro; Nat Dumrongmongcolgul; Michael Torres; Vasin Jungtrakoolchai (Case Reports in Pulmonology)
Bronchial varix is a rare pulmonary disorder which may lead to life-threatening hemorrhage. Diagnosis is difficult because of the subtle abnormalities on radiographic and bronchoscopic examination. We present a case of massive hemoptysis from a bleeding bronchial varix. In the absence of immediate complex endobronchial therapy in the island of Guam, this case was initially managed with nebulized and intravenous tranexamic acid. This was followed by endobronchial blockade of the bleeding airway with endobronchial epinephrine instillation. Selective bronchial artery embolization alleviated the acute-phase bleeding. Prone positioning was initiated due to severe hypoxia after blood clots compromised the patency of bilateral bronchial airways. Prone ventilation was employed for 17 hours for 2 consecutive days with intermittent bronchoscopic forceps extraction of airway blood clots while in the prone position. These maneuvers resulted to improved lung ventilation and oxygenation. The patient underwent bronchial sleeve resection surgery for definitive management.